STRATEGI PEMASARAN SYARIAH DALAM MENINGKATKAN LOYALITAS PELANGGAN DI PERBANKAN SYARIAH - Merlyn Anggraini; Iqbal Fasa, Muhammad (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2024)
This study analyzes the sharia marketing strategies employed by Islamic banks to enhance customer loyalty. Utilizing aqualitative approach, the research investigates variousstrategies that prioritize service quality and customerrelationships, drawing on data from relevant books andjournals. The findings reveal that high-quality service,customer relationship management (CRM), and sharia-compliant product innovation are essential factors in fostering customer loyalty. Adherence to sharia principles, personalized services, and continuous education regarding sharia productssignificantly contribute to building customer trust.Additionally, the adoption of digital technologies, such as online banking applications, has proven effective in improvingaccessibility and customer satisfaction. Despite challenges,including limited application socialization and uneveninternet access, this study concludes that effective shariamarketing strategies can strengthen customer relationships and expand the market share of Islamic banks within the banking sector.